IMPLEMENTASI DETEKSI WAJAH PADA SISTEM ABSENSI DENGAN MENERAPKAN TEKNIK FACE RECOGNITION - ZULFAHMI SYAHPUTRA (Unit Pengelola Jurnal Universitas Harapan Medan, 2022)
The development of technology is currently very fast in various fields of human life. One of the uses of technology is in the field of attendance. Attendance is the most important part in an institution, both educational, health, office and government agencies in supporting monitoring the daily attendance of employees. Klambir 5 Kebun Village is a village located in Hamparan Perak District, Kab. Deli Medium North Sumatra. Currently the attendance process at the Klambir 5 Kebun Village office still uses manual attendance. The use of manual attendance is considered to be less effective because if an employee arrives late, he can entrust his absence with another employee. Seeing this, the researchers designed an attendance system based on Face Recognition. Face recognition-based attendance is an attendance that is carried out using the detection of parts of the human face. Then in the design of an attendance system based on face recognition. With the construction of this attendance system, Klambir Village 5 Kebun can make attendance easier in every condition because it is based, then recapitulating the list of employees present at the village government is easier because it is already stored in a database